2020
DOI: 10.3390/jcm9030834
|View full text |Cite
|
Sign up to set email alerts
|

Correlates of Normal and Abnormal General Movements in Infancy and Long-Term Neurodevelopment of Preterm Infants: Insights from Functional Connectivity Studies at Term Equivalence

Abstract: Preterm infants born before 32 weeks gestation have increased risks for neurodevelopmental impairment at two years of age. How brain function differs between preterm infants with normal or impaired development is unknown. However, abnormal spontaneous motor behavior at 12-15 weeks post-term age is associated with neurodevelopmental impairment. We imaged brain blood oxygen level-dependent signals at term-equivalent age in 62 infants born at <32 weeks gestation and explored whether resting state functional conne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 47 publications
(60 reference statements)
0
18
1
Order By: Relevance
“…ASD). The prediction model is also capable of incorporating new and incoming subjects, a step further than previous within-sample imaging-outcome correlation studies ( Ball et al, 2015 ; Counsell et al, 2014 ; Deoni et al, 2016 ; Hintz et al, 2015 ; Keunen et al, 2017 ; Peyton et al, 2020 ; Wee et al, 2017 ; Woodward et al, 2006 ). Before the presented prediction can be used to identify individual infant at risk of neurodevelopmental disorders (e.g.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…ASD). The prediction model is also capable of incorporating new and incoming subjects, a step further than previous within-sample imaging-outcome correlation studies ( Ball et al, 2015 ; Counsell et al, 2014 ; Deoni et al, 2016 ; Hintz et al, 2015 ; Keunen et al, 2017 ; Peyton et al, 2020 ; Wee et al, 2017 ; Woodward et al, 2006 ). Before the presented prediction can be used to identify individual infant at risk of neurodevelopmental disorders (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Individual variability in brain structures and associated individual variability in future behaviors can be harnessed for robust prediction at the single-subject level ( Kanai and Rees, 2011 ; Rosenberg et al, 2018 ), a step further than group classification. A few studies have been conducted previously to investigate within-sample imaging-outcome correlations ( Ball et al, 2015 ; Counsell et al, 2014 ; Deoni et al, 2016 ; Hintz et al, 2015 ; Keunen et al, 2017 ; Peyton et al, 2020 ; Wee et al, 2017 ; Woodward et al, 2006 ), while such correlation approaches made it impossible to be applied to new and incoming subjects. Machine learning approaches that can adopt new subjects and yield continuous prediction values have been explored only recently based on WM structural networks ( Girault et al, 2019 ; Kawahara et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…Similar studies have also found comparable results to the current study. A study based on infants born VPT in the US showed that the MOS-R was independently related to Bayley-III motor, cognitive, and language outcomes in a multivariable model with the GMA [ 18 ]. Within the current study, the relationship of the MOS-R represented a much higher proportion of variance with the NSMDA than Bayley-III scores, suggesting that the MOS-R is better related to the NSMDA at 2 years’ CA.…”
Section: Discussionmentioning
confidence: 99%
“…A semi-quantitative measure that is an extension of the GMA, known as the Motor Optimality Score, revised 2019 (MOS-R) [ 15 , 16 ], provides an optimality score of an infant’s motor movements and patterns between 9 and 20 weeks’ CA. The MOS-R may provide a better association with later non-CP developmental outcomes [ 11 , 17 , 18 , 19 , 20 , 21 , 22 ] or indicate the severity of CP based on Gross Motor Function Classification System (GMFCS) grading [ 15 ], but while emerging evidence is encouraging, few studies have investigated the cut-off score to maximize predictive validity for motor, cognitive, or neurosensory impairment at 2 years’ CA. The MOS-R is conducted without assessor handling, a key advantage where face-to-face assessments may be limited, but requires additional advanced training beyond a basic general movements course.…”
Section: Introductionmentioning
confidence: 99%
“…The General Movements Assessment (GMA) is a key assessment for screening for cerebral palsy (CP) 1 and abnormal GMA is also related to developmental delay. 2,3 As an assessment that is evaluated from video recordings, 4 combined with the widespread availability of smartphone technology and reducing costs of electronics, 5 it is now possible to upskill parents/carers to record videos of their infants for clinical assessment. 6 While dedicated apps have been created to assist parents/carers to record and transmit videos, 7,8 much variance in organisational and regional privacy and data storage policy limits the use of a cost-effective one-size-fits-all phone app.…”
Section: What This Paper Addsmentioning
confidence: 99%